PENINGKATAN KEMAMPUAN MAHASISWA DALAM MENDESAIN DAN MENGEMBANGKAN ALAT PERMAINAN EDUKATIF (APE) MELALUI LESSON STUDY PADA MATA KULIAH TEKNOLOGI PEMBELAJARAN ANAK USIA DINI (AUD) - Intan Safiah (Jurnal Pencerahan, 2015)
This study aims to evaluate the ways to improve students' ability in designing and developing an Educational Game Equipment (EGE) and increasing the activity of students in the subject of Early Childhood Learning Technology (CLT). This research is the action research based on the lesson study model. In conducting the research, researcher assisted by colleagues to plan and conduct lectures for twice action study in order to improve students' ability in designing and developing the EGE and increasing the activity of the students in the instructional technology training courses of CLT. Data of the study were gathered from observation and questionnaires, which then was analyzed using the analysis of the average. The sample of the study was 34 students of Teacher Education-ECD, Faculty of Teacher Training and Education, Syiah Kuala University who were taking the courses of CLT Learning Technology at the second semester of academic year 2014/2015. Students were divided into 5 groups, resulting in product 5 EGE. The result showed that the activity of students in cycle 1 were in the very good category with the average score of 4.2 and the second cycle were in the very good category as well with the average score of 4.25. As for media design data of CLT, the result was in the category of very good with the average score of 4.5. Finally, in designing the APE, the study found the average score of 3.5, which was in the category of good.